2011
DOI: 10.1007/s10103-011-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of systemic photodynamic therapy in a leukemia animal model using A20 cells

Abstract: Photodynamic therapy (PDT) is attracting attention because of its noticeable inhibitory effects on the growth of dermatological and other solid tumors. Here, we studied the use of PDT in systemic diseases such as leukemia, lymphoma, and metastatic cancer, for which tumor formation areas cannot be clearly compartmentalized. We developed a systemic PDT method and examined its effect in a leukemia mouse model. Growth inhibition of A20 cells (H-2(d), murine B-lymphoma/leukemia, and Balb/c origin) induced by PDT/Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Cell viability was determined using EZ‐Cytox cell viability assay kit . Splenocytes, prepared as above, were seeded in a 96‐well plate (5 × 10 6 cells/mL) in a final volume of 100 µL in each well, and treated with various concentrations of N‐acyl dopamines (0–5 µM).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was determined using EZ‐Cytox cell viability assay kit . Splenocytes, prepared as above, were seeded in a 96‐well plate (5 × 10 6 cells/mL) in a final volume of 100 µL in each well, and treated with various concentrations of N‐acyl dopamines (0–5 µM).…”
Section: Methodsmentioning
confidence: 99%
“…The treatment efficacy of PDT against malignant tumors is hindered by the inherent aggregation-caused quenching (ACQ) effect of traditional PSs, the presence of antiapoptotic Bcl-2 in cells, and hypoxia in the tumor microenvironment [ 72 ]. Although Wen et al reported systemic PDT in a leukemic animal model with increased survival, the relative hypoxic microenvironment of lymphoma offsets the possible expansion of vascular PDT [ 73 , 74 ]. Nevertheless, with the aid of nanotechnology, enhanced PDT with a newer photosensitizer using multifunctional hybrid nanospheres shows a promising effect in both in vitro and in vivo animal models [ 72 , 75 ].…”
Section: Pros and Cons Of Pdt For Primary Cutaneous Lymphomasmentioning
confidence: 99%
“…In contrast to solid tumors, the application of PDT to hematological malignancies is a challenging process because basically these do not present on the skin or luminal surface where light can reach. In this regard, previous studies on animal experiments about in vivo PDT system for hematological malignancies [57,[86][87][88] and clinical studies of extracorporeal phototherapy using ultraviolet (UV-ECP) for mycosis fungoides (MF) and Sezary syndrome (SS) provide promising suggestions [89,90]. One preclinical study of an in-vivo animal model of PDT demonstrated that hematological cancer cells in peripheral blood could be directly killed by PDT.…”
Section: Pdt For Atl Cellsmentioning
confidence: 99%